2015
DOI: 10.2147/dddt.s81004
|View full text |Cite
|
Sign up to set email alerts
|

The brain signature of paracetamol in healthy volunteers: a double-blind randomized trial

Abstract: BackgroundParacetamol’s (APAP) mechanism of action suggests the implication of supraspinal structures but no neuroimaging study has been performed in humans.Methods and resultsThis randomized, double-blind, crossover, placebo-controlled trial in 17 healthy volunteers (NCT01562704) aimed to evaluate how APAP modulates pain-evoked functional magnetic resonance imaging signals. We used behavioral measures and functional magnetic resonance imaging to investigate the response to experimental thermal stimuli with AP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
25
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 50 publications
2
25
1
Order By: Relevance
“…Our study found that at rest, paracetamol FAAH-dependently decreased many spontaneous functional connections between critical structures involved in pain in subcortical regions such as the striatum, thalamus, PAG, the BNST, hippocampus, and basal forebrain region together with somatosensory, retrosplenial, cingulate, and insular cortices. In addition, the pain-evoked connectome observed during a noxious stimulation was drastically decreased in paracetamol-treated animals, again by an FAAH-dependent mechanism, suggesting that AM404 production by FAAH (Högestätt et al, 2005) (Pickering et al, 2015). Nevertheless, although these studies show that paracetamol can reduce pain-related activity of brain structures, they do not discriminate between peripheral and central location of its effect.…”
Section: Brain Connectome Modification During Paracetamol Challengementioning
confidence: 74%
See 1 more Smart Citation
“…Our study found that at rest, paracetamol FAAH-dependently decreased many spontaneous functional connections between critical structures involved in pain in subcortical regions such as the striatum, thalamus, PAG, the BNST, hippocampus, and basal forebrain region together with somatosensory, retrosplenial, cingulate, and insular cortices. In addition, the pain-evoked connectome observed during a noxious stimulation was drastically decreased in paracetamol-treated animals, again by an FAAH-dependent mechanism, suggesting that AM404 production by FAAH (Högestätt et al, 2005) (Pickering et al, 2015). Nevertheless, although these studies show that paracetamol can reduce pain-related activity of brain structures, they do not discriminate between peripheral and central location of its effect.…”
Section: Brain Connectome Modification During Paracetamol Challengementioning
confidence: 74%
“…Concerning paracetamol, a clinical Tc 99m SPECT imaging study reported a decrease in pain rating associated with a reduction of the cerebral blood flow in thalamus prefrontal cortex, sensorimotor area, anterior cingulate, and caudate nucleus after postoperative dental surgery in patients treated with paracetamol (Newberg et al, ). In addition, a clinical rs‐fMRI study performed in healthy volunteers demonstrated that paracetamol, compared with placebo, significantly reduced the pain‐related BOLD signal responses arising from noxious thermal stimulation, in insula, anterior cingulate cortices, prefrontal cortex, and thalamus (Pickering et al, ). Nevertheless, although these studies show that paracetamol can reduce pain‐related activity of brain structures, they do not discriminate between peripheral and central location of its effect.…”
Section: Discussionmentioning
confidence: 99%
“…A number of brain regions and cerebral interconnections have been described to be involved in predecisional processing and planning actions: parietal-frontal circuits, anterior cingulate and orbitofrontal cortices, and hippocampus 19,20. These cerebral areas and others are also activated during the pain experience; they belong to the pain matrix and have been shown to be deactivated by APAP as described by a recent functional magnetic resonance imaging study 18,21. Evidence from pharmacological experiments in humans has underlined the complex roles of dopamine and serotonin in decision making 22.…”
Section: Discussionmentioning
confidence: 99%
“…This test was chosen in the context of APAP effect on central structures looking for potential improvement of matching 18. The chosen outcome was the total number of trials for which the subject selected the correct stimulus on his or her first response when the target stimulus and the three distractors were presented after the stimulus had been hidden with delays of 0, 4,000, and 12,000 ms. A higher score is better.…”
Section: Methodsmentioning
confidence: 99%
“…Ottani et al [17] suggested that paracetamol could also have an effect on the endogenous cannabinoid system involving CB 1 receptors in the brain or spinal cord. Paracetamol also might inhibit pain sensation by decreasing the activation of higher brain structures (eg, anterior cingulate cortex or prefrontal cortices) involved in pain and cognitive/ affective processing [18].…”
Section: Summary Of the Evidence On Performancementioning
confidence: 99%